2019
DOI: 10.1111/ecc.13047
|View full text |Cite
|
Sign up to set email alerts
|

Savouring and psychological well‐being in family dyads coping with cancer: An actor–partner interdependence model

Abstract: Previous studies have investigated interdependence of the associations between predictors and negative psychological outcomes in dyads of cancer patients and family caregivers. This study examined the dyadic effects of perceived capability of savouring the moment on psychological well‐being. A total of 152 dyads of cancer patients and caregivers reported their perceived capability of savouring the moment (Savoring Beliefs Inventory), state positive affect (Chinese Affect Scale) and life satisfaction (Satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 58 publications
1
10
0
1
Order By: Relevance
“…Bloom and colleagues found that some caregivers of adults with cancer expressed more positive emotions than negative ones in their journal entries on online social media [ 27 ]. Caregivers often highlight the rewarding experience of caring and the joy of normal daily life [ 11 ••, 27 , 45 ]. The relationship between caregiver and patient may become more intimate due to a grateful experience of mutual support [ 34 ].…”
Section: Impact Of Caregiving On Informal Cancer Caregiversmentioning
confidence: 99%
“…Bloom and colleagues found that some caregivers of adults with cancer expressed more positive emotions than negative ones in their journal entries on online social media [ 27 ]. Caregivers often highlight the rewarding experience of caring and the joy of normal daily life [ 11 ••, 27 , 45 ]. The relationship between caregiver and patient may become more intimate due to a grateful experience of mutual support [ 34 ].…”
Section: Impact Of Caregiving On Informal Cancer Caregiversmentioning
confidence: 99%
“…According to interdependence theory, there is a strong interpersonal interaction between two individuals with intimate relationships (such as spouses-partners and patients-caregivers). Patients and caregivers are interdependent and influence each other (Hou et al, 2019;Kelley & Thibaut, 1978;Luo et al, 2019;Schellekens et al, 2017). For example, the personalities of people with close relationships affect not only their own depression but also that of their counterparts (Novak et al, 2017;Zayas et al, 2002).…”
Section: Personality Traits and Depressionmentioning
confidence: 99%
“…Itt a páciens a jelen pillanatban történő pozitív élmények élvezetére vonatkozó hite előrejelezte a családtagja pozitív érzelmi állapotát, míg a hozzátartozó jelenben történő savoringje pozitív irányú kapcsolatot mutatott a páciens élettel való elégedettségével. Az eredmények tehát ismételten megerősítették a pozitív élmények élvezetének fontosságát még a betegséggel árnyékolt helyzetekben is, amikor pozitív élmények esetlegesen ritkábban érik a párokat (Hou, Liang, Lau, & Hall, 2019).…”
Section: A Savoring Jelentősége a Páciens éS Az őT Támogató Környezet Számáraunclassified